EXPLORING TRUST IN TSUNAMI EVACUATION DECISION: AN INITIAL STUDY - Arini, Hilya Mudrika (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
This initial study explores the importance of trust in Aceh tsunami evacuation. Drawing upon the cultural theory as theoretical basis, this research classifies people in Aceh based on their trust level and identifies the significant factors influencing them to trust to different sources during tsunami. To accomplish the goals, an offline survey to 62 respondents in Aceh who experienced tsunami was conducted. From this survey, it found that most of respondents tend to be more trust to their self (individualist) and family/neighbor (egalitarian) than trust to government (hierarchy) and religious leader (traditional). On the other hand, (1) self-efficacy, (2) evacuation knowledge and (3) trust level to non-government people are indicated as the significant factors influencing people to trust in different sources during tsunami evacuation. This initial result will be benefit to develop a predictive model of trust using Agent-based model and simulation (ABMS) for the further research.